The Blockchain Phenomenon – The Disruptive Potential of Distributed Consensus Architectures - Juri Mattila (The Research Institute of the Finnish Economy (ETLA), 2016)
Blockchain technology is disrupting society by enabling new kinds of disintermediated digital platforms. Furthermore, it is also providing efficiency gains on top of old existing structures by removing the need for actively intermediated data-synchronization and concurrency control. Due to this dual effect, blockchain technology has the potential to impact all sectors and layers of society, in a multitude of combined ways. While there is a lot of hype around the concept of blockchains, the phenomenon itself has remained ambiguous and misconceptions have emerged about the capabilities and the potential of blockchain technology. Drawing from ETLA's participation in blockchain research in 2014–2016, this paper aims to provide a more comprehensive understanding on blockchain technology, its true possibilities, and its potential larger societal implications. It offers a holistic view of the key concepts and the basic principles, and the tools and the framework to understand the ongoing discussion, to critically evaluate different viewpoints, and to delve deeper in a constructed manner
Keywords: 330